An Experimental and Comparative Performance Evaluation of a Hybrid PV-TEG System for Energy Harvesting - Nur Auni Razali,; Norain Sahari, (Progress in Engineering Application and Technology, 2024)
The growing demand for sustainable and efficient energy sources has prompted the development of novel technologies that harness diverse energy sources. The goal of this project is to create a Hybrid Solar Thermoelectric Energy Harvesting System that combines the advantages of photovoltaic (PV) technology and thermoelectric generators (TEGs). Three separate case studies are carried out, including PV standalone, hybrid PV-TEG and hybrid PV-TEG with a heat sink and a small USB fan setups. Data gathering includes data such as temperature, voltage, current, and PV panel output power. The PV standalone scenario offers a baseline for typical solar energy conversion, whereas the following hybrid setups incorporate TEGs to investigate their combined potential. The addition of a heat sink and a small USB fan is intended to improve thermal management and system efficiency. The study intends to quantify the advances in energy harvesting and assess the practicality of the hybrid system for real-world applications through rigorous experimentation and data analysis. The findings of this study have important significance for the advancement of sustainable energy solutions, as they provide useful insights into the synergistic effects of integrating solar and thermoelectric technologies. The initiative adds to the continuing conversation about renewable energy systems and lays the path for the development of efficient, environmentally friendly power generation technologies.